2001
DOI: 10.1061/(asce)1090-0241(2001)127:11(965)
|View full text |Cite
|
Sign up to set email alerts
|

Simple Method of Modeling PVD-Improved Subsoil

Abstract: On a macroscale, the effect of installing prefabricated vertical drains (PVDs) in a subsoil is to increase the mass hydraulic conductivity of the subsoil in the vertical direction. Based on this concept, a simple method for modeling PVD improved subsoils is proposed, in which an equivalent vertical hydraulic conductivity k v e for the PVD improved subsoil is explicitly derived. With the proposed simple method, analysis of PVD improved subsoil is the same as that of the unimproved case. The theoretical verifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(118 citation statements)
references
References 11 publications
1
110
0
7
Order By: Relevance
“…A simple approximate method for modelling the effect of PVD is proposed by Chai et al (2001). Because PVD increases the mass permeability of subsoil in the vertical direction, it is logical to establish a value for vertical permeability which approximately represents the effect of vertical drainage of natural subsoil and radial permeability toward the PVD.…”
Section: Simple 1-d Modelling Of Vertical Drainsmentioning
confidence: 99%
“…A simple approximate method for modelling the effect of PVD is proposed by Chai et al (2001). Because PVD increases the mass permeability of subsoil in the vertical direction, it is logical to establish a value for vertical permeability which approximately represents the effect of vertical drainage of natural subsoil and radial permeability toward the PVD.…”
Section: Simple 1-d Modelling Of Vertical Drainsmentioning
confidence: 99%
“…Various conversion procedures have been proposed earlier (e.g. Shinsha et al 1982;Hird et al 1992;Bergado and Long 1994;Chai et al 2001;Indraratna et al 2005). Cheung et al (1991) employed the conversion procedure which assumes that the settlement response at 50% degree of consolidation is the same for both 2D and axisymmetric (3D) conditions (Shinsha 1991).…”
Section: Two-dimensional Plane Strain Finite Element Analysismentioning
confidence: 99%
“…The problem of water flow into a vertical drain under an infinitely wide fill is axisymmetric, and therefore the vertical drain system must be converted into an equivalent plane strain model for numerical simulations. Several authors ͑Hird et al 1992Chai et al 1995Chai et al , 2001Indraratna and Redana 1997͒ have shown that vertical drains can be effectively modeled by using appropriate mapping methods to represent the typical arrangement of vertical drains in plane strain finite-element analyses. However, certain simplifying assumptions are made, as discussed later on.…”
Section: Introductionmentioning
confidence: 99%
“…However, certain simplifying assumptions are made, as discussed later on. The two most useful mapping approaches from a computational point of view are those by Chai et al ͑2001͒ andHird et al ͑1992͒, as accounting for the effects of the smear zones around the drains does not require separate discretization. In this paper the combined mapping purposed by Hird et al ͑1992͒ is used in the analysis of the behavior of PVD improved subsoil in combination with complex elastoplastic models, namely MCC, S-CLAY1, and S-CLAY1S.…”
Section: Introductionmentioning
confidence: 99%